A Multibeam Solar Grid Antenna Integrated With Monocrystalline Silicon Solar Cell - Fuwei Wang; Xuechen Zhang; Rong Sun; Bokai Ding; Ke Li; Chen He (IEEE Open Journal of Antennas and Propagation)
This paper proposes a multibeam grid antenna integrated with a monocrystalline silicon solar panel first time, which consists of a grid antenna in microstrip form and a monocrystalline silicon solar cell. Multiple feeders are set at different positions of the grid antenna to adjust the current phase on the short side of the grid antenna to achieve beam scanning. The antenna is designed to operate in the 24 GHz radar band and can be installed in field Internet of Things devices for vehicle monitoring and communication, meeting requirements for communication rate, sensing sensitivity, detection, and interconnectivity. The multibeam characteristic can effectively enhance the communication and sensing detection range of the antenna. Meanwhile, the grid-like structure of the antenna ensures good optical transmission, allowing it to be positioned above the solar panel without significantly affecting the performance of the solar cell. The measurement results show that the multibeam solar grid antenna can cover the 24 GHz radar band and achieve beam deflection in four azimuth planes with a gain range of 15.2 to 16.6 dBi at the center frequency of 24.125 GHz. And the solar panel can supply a voltage of 0.56 V. The proposed antenna can realize the power supply and wide-range communication and detection for Internet of Things systems, which has great potential for application.